Achieving tolerance modifies cancer susceptibility profiles in liver transplant recipients. (7th October 2022) - Bhat, Mamatha; Pasini, Elisa; Patel, Preya; Yu, Jeffrey; Baciu, Cristina; Kurian, Sunil M.; Levitsky, Josh
Abstract: Long‐term survival of transplant recipients is significantly impacted by malignancy. We aimed to determine whether calcineurin inhibitor (CNI)‐treated recipients converted to and weaned off molecular target of rapamycin inhibitor (mTOR‐I) therapy have favorable changes in their molecular profiles in regard to malignancy risk. We performed gene expression profiling from liver biopsy and blood (PBMC) specimens followed by network analysis of key dysregulated genes, associated diseases and disorders, molecular and cellular functions using IPA software. Twenty non‐immune, non‐viremic patients were included, and 8 of them achieved tolerance. Two comparisons were performed: (1) tolerance time point vs tacrolimus monotherapy and (2) tolerance time point vs sirolimus monotherapy. Upon achieving tolerance, IPA predicted significant activation of DNA damage response ( p = 5.40e‐04) and inhibition of DNA replication ( p = 7.56e‐03). Conversion from sirolimus to tolerance showed decrease in HCC ( p = 1.30e‐02), hepatic steatosis ( p = 5.60e‐02) and liver fibrosis ( p = 2.91e‐02) associated genes. In conclusion, this longitudinal study of patients eventually achieving tolerance reveals an evolving molecular profile associated with decreased cancer risk and improved hepatic steatosis and liver fibrosis. This provides a biological rationale for attempting conversion to mTOR‐I therapy and tolerance following liver transplantation particularly in patients at higher risk of cancer incidence and progression post‐transplant. Abstract : Achieving tolerance modifies cancer susceptibility profiles in liver transplant recipients. Liver transplant patients who weaned off sirolimus therapy have favorable changes in their molecular profiles in regard to malignancy risk.